Psychiatric Acute Day Hospital as an Alternative to Inpatient Treatment - Heekeren, Karsten; Antoniadis, Sofia; Habermeyer, Benedikt; Obermann, Caitriona; Kirschner, Matthias; Seifritz, Erich; Rössler, Wulf; Kawohl, Wolfram (Frontiers in Psychiatry, 2020)
For the first time in the Swiss healthcare system, this evaluation study examined whether patients with acute psychiatric illness who were admitted for inpatient treatment could be treated in an acute day hospital instead. In addition, it was examined whether and to what extent there are cost advantages for day hospital treatment. Patients who were admitted to the hospital with a referral to an inpatient admission were treated randomly either fully inpatient or in the acute day hospital. As a pilot study, 44 patients were admitted to the study. Evidence of efficacy could be provided for both treatment settings based on significant reduction in psychopathological symptoms and improvement in functional level in the course of treatment. There were no significant differences between the two settings in terms of objective and subjective symptom burden, functional level, quality of life, treatment satisfaction and number of treatment days. Treatment in the day hospital was about 45 percent cheaper compared to inpatient treatment. The results show that acutely ill psychiatric patients can be treated just as well in an acute day hospital instead of being admitted to the hospital. In addition, when direct treatment costs are considered, there are clear cost advantages for day hospital treatment.